2000
DOI: 10.1063/1.1286727
|View full text |Cite
|
Sign up to set email alerts
|

Electron transport mobility in a δ-doped double quantum well structure

Abstract: The electron transport mobility μn in a GaAs/AlxGa1−xAs coupled double quantum well structure has been studied. The central barrier is delta-doped with Si so that we have two sheets of two dimensional electron gas separated by a positively charged donor layer. The subband electron wave functions and the energy levels are numerically obtained as a function of barrier height, barrier width, well width, and doping concentration. The screened ionized impurity potential is obtained in terms of the static dielectric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 26 publications
0
20
0
2
Order By: Relevance
“…The intersubband scattering not only allows more scattering channels, but also affects the screened impurity potential V eff nm (q) by involving all the subbands of the system (eqn (23)). In our formulation screening of ionized impurities has been obtained by using random phase approximation (RPA), which has been proved successful for practical numerical calculations of electron transport mobility in a multisubband system [5][6][7]17]. We note that because of the finite potential barrier there will be electron penetration into it.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intersubband scattering not only allows more scattering channels, but also affects the screened impurity potential V eff nm (q) by involving all the subbands of the system (eqn (23)). In our formulation screening of ionized impurities has been obtained by using random phase approximation (RPA), which has been proved successful for practical numerical calculations of electron transport mobility in a multisubband system [5][6][7]17]. We note that because of the finite potential barrier there will be electron penetration into it.…”
Section: Resultsmentioning
confidence: 99%
“…It is gratifying to note that the screening, which is determined by the dielectric matrix eqn (13), is also discontinuous at the higher subband occupancy and results in a discontinuous scattering matrix element which leads to an increase in the intrasubband terms, say, B 00 . In fact it has been shown that the change in B 00 is the major contribution for the drop in mobility at the onset of occupation of a higher subband [17].…”
Section: Subband Transport Mobilitymentioning
confidence: 98%
“…In the present paper we analyze electron transport mobility in a barrier ␦-doped GaAs/ In x Ga 1−x As double quantum well structure. Unlike the GaAs/ Al x Ga 1−x As systems, [12][13][14][15] here the well region is the alloy layer ͑InGaAs͒ and hence we consider the effect of alloy disorder scattering in addition to the ionized impurity scattering for the calculation of n . The merits of GaAs/ In x Ga 1−x As strained layer 1,2 and advantages of ␦ doping in the barrier region of the heterostructure [16][17][18] have been employed to analyze n .…”
Section: Introductionmentioning
confidence: 99%
“…The electron transport in such multisubband occupied systems has been shown to be influenced by intersubband interactions. [17][18][19][20][21][22] In a recent paper 22 we studied the effect of intersubband interaction on the subband mobility of a coupled GaInP/GaAs double quantum well structure. We showed that the intersubband interaction not only controls the effect of roughness of different interfaces but also exhibits interesting results on the well width up to which the interface roughness ͑IR͒ dominates in a double quantum well structure.…”
Section: Introductionmentioning
confidence: 99%